Thinking about escaping poverty : a critical argument analysis identifying the conceptualisation of constraints to poverty reduction implicit in the Johannesburg human development strategy - Van Dongen, Lisa (Department of Political Studies, 2014)
Includes bibliographical references (leaves 91-103).